Mechanism of Cutting Elastomers with Cryogenic Cooling. Issue 1 (2016) - Putz, Matthias; Dix, Martin; Neubert, Mike; Schmidt, Torsten
Abstract: Machining of elastomers offers more flexibility of product shape in comparison to the common compression moulding, especially for small batch series. In this context the entropy-elastic behaviour of the material with low Young's modulus is the main barrier for high-quality manufacturing. This material behaviour could be temporarily adapted by cryogenic cooling for precise cutting. In this article, the different mechanisms, e.g. forces, friction and separation procedures, are analysed for elastomers with different material behaviours. Different chip formation mechanisms are shown in comparison to metal machining. As a result, the friction ( μ  ≈ 1) between work piece, chip and tool dominates. An analytic chip formation model has been applied.